2018
DOI: 10.2174/0929866524666170711120501
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Characterization of a New Type of Lectin with α-Amylase Inhibitory Activity in Chickpea (Cicer arietinum L.)

Abstract: Identification by Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC/MS-MS) indicated that the purified proteinaceous α-amylase inhibitor was a chickpea lectin CAL in GenBank (accession No. AGL46982.1). CAL had 227 aa containing a hemopexin- like repeats domain and was a cytoplasm protein. It had very low (<17%) identity with seven members in the lectin-arcelin-aAI1 supergene family in legumes that have α-amylase inhibitory activity. The purified CAL derived from prokaryotic expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous reports of chickpea lectin on various facets include characterization of a clone encoding vegetative lectin from Cicer arietinum epicotyls (Esteban et al 2002), production of stable transgene chickpea through expression of insecticidal lectin (Chakraborti et al 2009) and root lectins (Agrawal et al 2011). In addition, in silico studies on recombinant chickpea lectin (Wakankar et al 2013), three dimensional structure determination (Sharma et al 2015) and a-amylase inhibitory activity against potato beetle larvae (Wang et al 2017) are also available in literature domain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports of chickpea lectin on various facets include characterization of a clone encoding vegetative lectin from Cicer arietinum epicotyls (Esteban et al 2002), production of stable transgene chickpea through expression of insecticidal lectin (Chakraborti et al 2009) and root lectins (Agrawal et al 2011). In addition, in silico studies on recombinant chickpea lectin (Wakankar et al 2013), three dimensional structure determination (Sharma et al 2015) and a-amylase inhibitory activity against potato beetle larvae (Wang et al 2017) are also available in literature domain.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that CAL is not part of the lectin-arcelin-aAI1 supergene family. The IC 50 value was not indicated [ 39 ].…”
Section: Peptides Against Obesity and Insulin Resistancementioning
confidence: 99%
“…Chickpea possesses high-quality starch, protein, fat and dietary fiber ( 3 ), and plays an important role in human diets. Previous studies have shown that chickpea possesses various biological activities, such as antioxidant ( 4 ), anti-inflammatory ( 5 ), amylase inhibitor ( 6 ), and angiotensin I-converting enzyme (ACE) inhibitory ( 7 ) activities.…”
Section: Introductionmentioning
confidence: 99%